Geochemical Evidence Constraining Genesis and Mineral Scaling of the Yangbajing Geothermal Field, Southwestern China - Yang, Hu; Yuan, Xingcheng; Chen, Yongling; Liu, Jiawei; Zhan, Chun; Lv, Guosen; Hu, Junfeng; Sun, Minglu; Zhang, Yunhui (Water (Basel), 2024)
The Yangbajing geothermal field, a renowned high-temperature geothermal resource in Tibet of southwestern China, has been utilized for power generation for several decades. To improve geothermal exploitation in the Yangbajing, genesis and mineral scaling have yet to be further revealed. In this study, hydrochemistry and D-O-Sr isotopy were employed for analyzing genesis and mineral scaling in the Yangbajing geothermal field. The geothermal waters were weakly alkaline and had a high TDS content (1400–2900 mg/L) with the Cl-Na, Cl·HCO3-Na, and HCO3·Cl-Na types. The dissolution of silicate minerals (sodium and potassium feldspars) and positive cation exchange controlled the hydrogeochemical process. The geothermal water was recharged from snow-melted water and meteoric water originating from the Nyainqentanglh Mountains and Tangshan Mountains. The geothermal waters possessed the highest reservoir temperature of 299 °C and the largest circulation depth of 2010 m according to various geothermometers. The geothermal waters can produce CaCO3 and SiO2 scaling during vertical and horizontal transport. These achievements can provide a scientific basis for the sustainable development and conservation of the high-temperature geothermal resources in Yangbajing and elsewhere.